EXPRESSIVE ILLOCUTIONARY ACTS IN THE FILM CAPTAIN AMERICA THE FIRST AVENGER - Heraldine, Monica; Ambalegin, Ambalegin (IdeBahasa, 2025)
The purpose of this qualitative descriptive research was to identify the expressive illocutionary acts and the functions theorized by Searle & Vanderveken and Leech in film “Captain America the First Avenger”. An observational method was used in this study's data collection process, which involved watching the film. Since it was not a direct participant in the conversation, practical technique used in this research was non-participant technique. This study employed data reduction to reduce redundancy in data analysis and the pragmatic identity method in the equalizing procedure. In terms of how the research findings were presented, it used an informal method that was connected to the words and sentences used to describe the findings. Thirteen expressive illocutionary acts were found. The actions include welcome, lament, praise, boast, protest, condole, apologize, congratulate, thank, complain, complement, deplore, and greet. The act of complain was the dominant act because the characters frequently display sentiments of unease, melancholy, and disappointment to their conversation partners. The research served four functions, thus are convivial, collaborative, competitive, and conflictive. Therefore, the characters' most common function was convivial. The reason is that the things they said had social goals in them, such as saying hello, welcoming, thanking, and celebrating.